Stackelberg equilibrium-based energy management strategy for regional integrated electricity–hydrogen market - Wang, Qinghan; Wang, Yanbo; Chen, Zhe (Frontiers in Energy Research, 2023)
This paper develops an optimal energy bidding mechanism for regional integrated electricity-hydrogen system (RIEHS) considering complex electricity-hydrogen energy flow, and further presents an electricity-hydrogen optimization management strategy based on Stackelberg game. The transaction mode of RIEHS is first introduced, and the optimization models for the three market game participants are established. Then, the Stackelberg game-based bidding mechanism is formulated, where electricity-hydrogen operator (EHO) is the leader and regional electrical-hydrogen prosumer (REHP) and load aggregator (LA) are the followers. EHO dominates the game through energy bidding, and REHP and LA respond the bidding decision. The Stackelberg equilibrium of the formulation is obtained by applying differential evolutionary algorithm combined with quadratic programming (DEA-QP). Finally, a demonstration case is studied to analyze the market behavior of the three market players and further validate the effectiveness of the proposed strategy. The proposed strategy is able to produce additional economic benefits to REHP and LA and improve the utilization of hydrogen.